Chemical composition and bioactivities of Phellinus pini extracts, and quality evaluation of healthy drinks prepared from the mushroom - Ngan Nguyen Thi; Nguyen Trang H.D. (Journal of the Serbian Chemical Society)
Phellinus pini, a mushroom species found in East Asian countries, is commonly consumed as a medicinal beverage known for its stomach-warming effects and purported ability to alleviate pain and tumours. In this study, P. pini was extracted using different methods (hot water, sonication, microwave, and soaking). The extracts were analysed for phenolic and polysaccharide contents. Additionally, the extracts were evaluated for their antioxidant potential and ability to inhibit albumin denaturation. The results demonstrated that the extract obtained with hot water extraction contained the greatest amount of phenolics (105.98±0.53 mg GAE/mL). The hot water and microwave extraction methods showed more effective in extracting polysaccharide from the mushroom. Moreover, the extract from the ultrasound extraction method presented the strongest antioxidant activity by scavenging DPPH and ABTS radicals by 41.26 and 97.84 %, respectively while the hot water extract exhibited the most potent ability to inhibit albumin denaturation by 96.40 %. Among the four healthy drinks formulated, the formulation with the greatest proportion of P. pini extract contained the highest total phenolic content, antioxidant activity, and the most favorable sensory overall liking. The described findings deepen our understanding of the chemical composition and potential health-promoting properties of P. pini, as well as revealing new potential applications for the mushroom in the food and nutraceutical industries.